A study on the pathogenicity of Elizabethkingia meningoseptica in treated African catfish with excoecaria agallocha via metabolomics profiling - Abdul Razzak, Laith A (Terengganu: Universiti Malaysia Terengganu, 2014)
Elizabethkingia meningoseptica is one of the most significant bacterial species for human infections. At present, no data is avalaible on E. meningoseptica infection in diseased freshwater fish. This study was carried out to investigate E. meningoseptica infection in freshwater cultured African catfish.